Acute Kidney Injury Caused By Superior Mesenteric Artery Syndrome - Nur Ezzaty Mohammad Kazmin; Lydia Kamaruzaman; Voon Ken Fong; Ruslinda Mustafar; Rozita Mohd; Zhiqin Wong (Hindawi Limited, 2024)
Background. Superior mesenteric artery (SMA) syndrome is a rare cause of upper gastrointestinal obstruction leading to acute kidney injury (AKI). Methods. We report a case of 23-year-old army personnel who presented with persistent vomiting leading to severe hypokalaemia, metabolic alkalosis, and acute kidney injury resulting in cardiorespiratory arrest. Results. After successful resuscitation, he was supported with haemodialysis and aggressive electrolytes correction. He was repeatedly not able to tolerate nasogastric (NG) tube feeding and computerised tomography of abdomen was performed, and the diagnosis of SMA syndrome was made. Gastroscopy examination revealed duodenal ulcer at D1, pinhole D1-D2 junction, but there was no evidence of intraluminal mass or lesions leading to upper gastrointestinal obstruction. A nasojejunal tube was inserted to bypass the narrow segment of the duodenum, and he was put on nutritional support. He was subsequently weaned off dialysis support as his renal function gradually improved and later on normalised. He remains symptoms free, and he gained five kilograms in four months after discharge. Conclusions. SMA syndrome is a rare cause of upper gastrointestinal obstruction but should be considered as a differential diagnosis in a patient who presented with recurrent vomiting and AKI with metabolic alkalosis.